Knowledge of genito-urinary syndrome of menopause among Italian gynecologists: the DIADEM survey. (January 2021) - Alvisi, Stefania; Baldassarre, Maurizio; Gava, Giulia; Mancini, Ilaria; Cagnacci, Angelo; Seracchioli, Renato; Meriggiola, Maria Cristina
Highlights: Italian gynecologists have some knowledge of GSM, but they underestimate its prevalence. Knowledge of treatment efficacy and women's compliance seems inadequate. Up-to-date flow-charts of available treatments are lacking. Abstract: Objective: The objective of this study was to present an updated picture of the knowledge and attitudes of Italian gynecologists with regard to the genitourinary syndrome of menopause (GSM). Study design: An anonymous survey was sent via electronic mail to 3892 gynecologists. The survey consisted of 32 multiple-choice questions divided into four different areas: 1. general demographics of the respondents; 2. knowledge of GSM; 3. most frequently prescribed therapies; and 4. perception of patient compliance and satisfaction with current therapeutic options. Main outcome measures: Knowledge of vulvo-vaginal atrophy (VVA) and attitudes of the gynecologists to its management. Results: Three hundred and seventy-four out of 3892 invited Italian gynecologists replied to the survey (response rate 9.7 %). Most (84 %) had a good knowledge of GSM and 74 % reported that they investigated it during clinic visits, but most of them underestimated its prevalence. The most frequently prescribed treatment was topical hormonal therapy (60 %), followed by vaginal moisturizers and lubricants (16 %), ospemifene (12 %) and systemic hormone therapy (12 %). According to the clinical experience of respondents, the most effective therapy is local hormonal therapy (36 %), followed by ospemifene (30 %). According to respondents, less than 50 % of patients continue therapy after 12 months, due to the discomfort in vaginal application, the cost of oral therapies and the fear of possible side-effects. Conclusions: With the limitation of the low response rate, this study suggests that although Italian gynecologists who answered the survey had some knowledge of GSM, they underestimated its prevalence, did not know its most bothersome symptoms and had inadequate knowledge of the efficacy of treatments, patient compliance and satisfaction.